ENTRE A DITADURA E A DIÁSPORA: uma análise à emigração portuguesa dos anos 60 - Loureiro, Clara (2024)
This article aims to begin a detailed analysis of the Portuguese emigration during the 1960s, with the main objective of understanding the underlying reasons and describing a chronological line that explains the topic. Likewise, focus will be placed on migratory flows, to the same extent as the alternation between the main destination countries chosen by the Portuguese population, on different continents, will be studied. We will also seek to account for the impact of forced emigration, in the context of the Colonial War, through an empirical but also practical basis.